2014
DOI: 10.1073/pnas.1406165111
|View full text |Cite
|
Sign up to set email alerts
|

Stone tools from the ancient Tongan state reveal prehistoric interaction centers in the Central Pacific

Abstract: Tonga was unique in the prehistoric Pacific for developing a maritime state that integrated the archipelago under a centralized authority and for undertaking long-distance economic and political exchanges in the second millennium A.D. To establish the extent of Tonga's maritime polity, we geochemically analyzed stone tools excavated from the central places of the ruling paramounts, particularly lithic artifacts associated with stone-faced chiefly tombs. The lithic networks of the Tongan state focused on Samoa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 28 publications
1
75
1
Order By: Relevance
“…The most parsimonious explanation would be a significant mobility wherein people moved around both within the island and between nearby islands collecting and consuming a range of foods. Different geographical origins have been identified in the raw material of obsidian (north Tonga) and stone artifacts (south and central Tonga and east Fiji) (Reepmeyer et al, 2012;Clark et al, 2014). (Tables 4 and 5, for individual data see SD2): Vanuatu (Valentin et al, 2010, Bismarck Islands (Petchey and Green, 2005;Kinaston et al, 2015), and Fiji (Nunn et al, 2007; show an overlap of the collagen values, except for the female (Sk3.1), highlighting again her different dietary regime (Fig.…”
Section: Highlighting Inter-individual Isotope Variabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…The most parsimonious explanation would be a significant mobility wherein people moved around both within the island and between nearby islands collecting and consuming a range of foods. Different geographical origins have been identified in the raw material of obsidian (north Tonga) and stone artifacts (south and central Tonga and east Fiji) (Reepmeyer et al, 2012;Clark et al, 2014). (Tables 4 and 5, for individual data see SD2): Vanuatu (Valentin et al, 2010, Bismarck Islands (Petchey and Green, 2005;Kinaston et al, 2015), and Fiji (Nunn et al, 2007; show an overlap of the collagen values, except for the female (Sk3.1), highlighting again her different dietary regime (Fig.…”
Section: Highlighting Inter-individual Isotope Variabilitymentioning
confidence: 96%
“…and Tridacna spp., and small circular flat beads that are similar to Lapita ornaments. Lithics items comprise adzes, flakes, grinding stones and oven stones whose raw material has a distinct geographical source with obsidian from northern Tonga and lithics from 'Eua (south Tonga), Samoa, east Fiji and volcanic islands within Tonga, suggesting significant population mobility (Reepmeyer et al, 2012;Clark et al, 2014). The deposit also includes features, such as 'hearths, ovens, oven rake outs, and burials, placed at the base of the deposit or interstratified within the midden.…”
Section: Talasiu Sitementioning
confidence: 99%
“…Postcolonization voyaging between islands was essential for securing a lifeline between parent and daughter communities (e.g., ref. 9), to obtain prestigious commodities from distant islands for elites (10), and for integrating far-flung communities under a centralized authority, such as the Tongan maritime state (11). Some, however, have opined that postcolonization voyaging and artifact transfer in East Polynesia were minimal (7,12).…”
mentioning
confidence: 99%
“…The major sources of fine-grained basalt, the singular raw material used for adze manufacture across tropical Polynesia, are restricted to a few known localities. Previous studies have shown that these essential tools were sometimes transported more than 1,000 km within interaction spheres involving exchanges of goods and services (11,(13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation